INFLUENCE OF SOY MILK CONSUMPTION ON REDUCING HOT FLUSHES IN PRE-MENOPAUSAL WOMEN IN SIUMBUT BARU WARD I YEAR 2025 - Meity Christiani; Joharmi lutfhi; Ustifina Hasanah Hasibuan; Dinda Purnama DS (Benih : Journal of Midwifery, 2025)
Hot flush is one of the common vasomotor symptoms experienced by women during pre-menopause due to decreased estrogen levels. Soy milk contains phytoestrogens (isoflavones) that act similarly to estrogen and are believed to reduce hot flush symptoms. This study aimed to determine the effect of soy milk consumption on reducing hot flush among pre-menopause women in Siumbut New Village in 2025. This was a quantitative study using a one-group pretest-posttest design. The sample consisted of 30 pre-menopause women selected by purposive sampling. The intervention was the daily consumption of soy milk (1 glass per night) for 14 consecutive days. Data were collected using observation sheets and analyzed with the Wilcoxon Signed Rank Test. Before the intervention, most respondents experienced severe (43.3%) and very severe (56.7%) hot flush symptoms. After the intervention, 60% of respondents reported no hot flush and 40% reported mild symptoms. The Wilcoxon test showed a significant difference (Z = -4.855, p = 0.000; p < 0.05), indicating that soy milk consumption effectively reduced hot flush symptoms. Conclusion: Soy milk consumption has a significant effect in reducing hot flush among pre-menopause women. It may be considered a safe and natural non-pharmacological alternative for managing menopause symptoms.